The effect of the toxin on the structural organization of the endothelial cells of the lymph node (Eurasian Journal of Ecology, 2016)
At chronic intoxication essential ultrastrukturyny violations happen chloride cadmium in the endoteliotsitakh of a deep cervical lymph node of animals. These changes are characterized by violations of power supply of cages,decrease in their beloksintetichesky function. In lymph nodes of the animals receiving after poisoning of Tagansorbent, less expressed structural changes were noted. For 21 days in the endoteliotsitakh there was a partial restoration of beloksintetichesky and power forming function of cages to what restoration to initial level of membranes granular endoplasmic ретикулума, free the polisomalnykh of ribosomes and structure of mitochondrions testifies. Therefore, Tagansorbent's 21 day using has protective impact on the stukturno-functional organization of hepatic cages at cadmicintoxication.
Keywords: lymph node; endotheliocyte; toxin; Tagansorbent; cadmium chloride; homeostasis; the ribosome; microporosity the vesicles; mitochondria; numerical density; bulk density.